The Gravity Model for Assessing Trade Patterns: the Case of Baltic States - Čipkutė, Eivilė (Ekonomika, 2017)
International trade is the key element of globalisation and closer economic and political cooperation between countries. Regional integration is an important driver of closer trade ties among countries. In this context, the article focuses on analysing the factors, influencing the dynamics of trade patterns of the Baltic States. The research method used in the article is the gravity model of trade, which rests on the key assumption that trade between countries is defined by the size of the economies and the distance between the countries. The gravity equation estimates showed that the membership of the Baltic States in the EU had a positive effect on the export levels of the Baltic States to other EU members. On the other hand, the membership in the EU is not the main trade stimulating factor. The more important factor for the Baltic States’ exports is the former economic ties with Russia. An analysis also revealed that the Baltic States have many important trade partners with different levels of income. This finding does not support the Linder hypothesis which states that the main trading partners should have a rather similar level of income.
Keywords: gravity model of trade; trade patterns; international trade; Linder hypothesis